Technical study of Germolles’ wall paintings: the inputof imaging technique - Christian Degrigny; Francesca Piqué; Nutsa Papiashvili; Julien Guery; Alamin Mansouri; Gaëtan Le Goïc; Vincent Detalle; Dominique Martos-Levif; Aurélie Mounier; Stefanie Wefers; Cristina Tedeschi; Marco Cucchi; et al. (Virtual Archaeology Review, 2016)
The Château de Germolles is one of the rare palace in France dating from the 14th century. The noble floor is decorated with wall paintings that are a unique example of courtly love spirit that infused the princely courts of the time. After being concealed sometime in the 19th century, the paintings were rediscovered and uncovered in the middle of the 20th century and partly restored at the end of the 1990s. No scientific documentation accompanied these interventions and important questions, such as the level of authenticity of the mural decorations and the original painting technique(s) used in the medieval times remained unanswered. The combined scientific and financial supports of COSCH Cost Action and DRAC-Burgundy enabled to study Germolles’ wall paintings using some of the most innovative imaging and analytical techniques and to address some of the questions raised. The study provided significant information on the material used in the medieval times and on the conservation condition of the paintings. The data collected is vast and varied and exposed the owners of the property to the challenges of data management.